Rights, wrongs, and injustices: the structure of remedial law - Smith, Stephen A. (Oxford Private Law Theory, 2019)
Rights, Wrongs, and Injustices is the first comprehensive account of remedial law’s scope, foundations, and structure. A remedy, it argues, is a judicial ruling, and remedial law is the body of rules governing the availability and content of remedies. Focusing on rulings that are intended to resolve private law disputes (e.g. awards of damages, injunctions, and restitutionary orders), this book explains why remedial law is distinctive, how it relates to substantive law, and what its foundational principles are. Drawing on doctrinal, historical, and philosophical sources, it advances four main arguments. First, the question of what courts should do when individuals seek their assistance (the focus of remedial law) is different from the question of how individuals should treat one another in their day-to-day lives (the focus of substantive law). Second, remedies provide distinctive reasons to perform the actions they command; in particular, they provide reasons different from those provided by either rules or sanctions. Third, remedial law has a complex relationship to substantive law. Some remedies are responses to rights-threats, others to wrongs, and yet others to injustices. Further, remedies respond to these events in different ways: while some remedies replicate substantive duties, others modify duties or create entirely new duties. Finally, remedial law is underpinned by general principles—principles that cut across the traditional distinctions between so-called ‘legal’ and ‘equitable’ remedies. Together, these arguments provide the foundation for an understanding of remedial law that takes the concept of a remedy seriously, classifies remedies according to their grounds and content, illuminates the relationship between remedies and substantive rights, and explains remedial law in terms of general principles, not historical categories.